Nutrition now - Brown, Judith E. (Wadsworth/Cengage Learning, 2008)
NUTRITION NOW is your best option to learn about basic nutrition principles and ways you can make the right decisions for meeting your own nutrition needs. The applied, consumer-oriented approach puts you in the driver seat and will show you that there is a lot to learn about the science of nutrition. Additionally, the unique modular format, comprised of 32 individual units, focuses the content into manageable chunks, making it easier to read and retain the material. This edition incorporates up-to-date coverage of the newest research and emerging issues in nutrition. The interactive pedagogical features of this text, along with the author's direct and friendly writing style, make it a favorite among readers. There is also a new "Interactive Learning Guide" available that includes a variety activities that will help you assess and apply your new found knowledge